Severe Influenza A (H1N1) is the Pathological Anatomy of the Lung - A. L. Chernyaev; O. V. Zairatyants; A. G. Chuchalin; L. M. Mikhaleva; Ye. I., Kelli; K. A. Rogov; M. V. Samsonova; V. M. Pominalnaya; A. Ye. Trusov; N. A. Bukhtoyarova (Общая реаниматология)
Twenty-five autopsy cases of influenza А (НШ1) in Moscow were analyzed. Primary pathological changes were found in the trachea and lung. The lung showed a pattern of the exudative and proliferative stages of diffuse alveolar damage. In addition, there were signs of infectious-toxic shock associated with viremia. Bacterial bronchopneumonia with confluent foci was detected in only 20% of the dead cases. Key words: influenza А (НШ1), diffuse alveolar damage.